Implementasi Kognisi Sosial dalam Berita Tribunnews.com Tersandung Korupsi 271 Triliun, Harta Kekayaan 3 Mantan Pejabat Timah Mencapai Puluhan Miliar : Perspektif Van Dijk - Alfarizqo, Muhammad (sarasvati, 2025)
This research was conducted with the aim of understanding the thought process of the discourse in writing a critical discourse. This research uses a descriptive qualitative research method. In this study, an approach based on Van Dijk's theory was used by focusing the research on the aspect of social cognition. This study found that there are aspects of social cognition that intersect in the news text "Stumbled upon Corruption of Rp 271 Trillion, the Wealth of 3 Former PT Timah Officials Reaches Tens of Billions" when viewed through the aspects of knowledge, opinions and attitudes, and figures.